Two Pathogenic Fungi Isolated From Chalkbrood Samples and Honey Bee Viruses They Carried - Cheng, Xuefen; Zhang, Li; Luo, Ji; Yang, Sa; Deng, Yanchun; Li, Jianghong; Hou, Chunsheng (Frontiers in Microbiology, 2022)
Ascosphaera apis and some Aspergillus species are the main pathogenic fungi of honey bee, and A. apis is the pathogen of chalkbrood disease. However, the infection mechanism of them is incompletely known and it is still unclear whether other factors impact their pathogenesis. In this study, Aspergillus tubingensis were obtained from the chalkbrood bee samples for the first time. Our results showed that A. tubingensis could promote the accumulation of the spores of A. apis. Pathogenicity test found that inoculation of the spores of the two fungi alone or their combination could induce disease characterization of chalkbrood and stonebrood but the extent was less than those in field. To further identify other pathogens impacted the pathogenesis, we found several honey bee viruses presented in the pathogenic fungi A. apis and A. tubingensis, which were different from previous reported. Our results indicated that acute bee paralysis virus (ABPV) and chronic bee paralysis virus (CBPV) could replicate in these two fungi and increased in titer with the going of cultivation time. In addition, CBPV could not only transmit vertically to the next generation by spores, but also spread horizontally to different fungi through hyphal anastomosis. These results suggested that the honey bee chalkbrood contained the other pathogenic fungi besides A. apis, the interactions between different pathogens of chalkbrood microbial communities may influence the prevalence of chalkbrood. Moreover, the discovery of honey bee viruses and their transmission mode in these two fungi enhanced the potential of exploring fungi virus as valuable factors that cause fungal disease outbreak.